Magnetic Nanoparticle-Based Dispersive Solid-Phase Microextraction of Three UV Blockers Prior to Their Determination by HPLC-DAD - Abughrin, Suad E.; Alshana, Usama; Bakirdere, Sezgin (MDPI, 2022)
The need for proper handling of environmental samples is significant, owing to their environmental effects on both humans and animals, as well as their immediate surroundings. In the current study, magnetic nanoparticle-based dispersive solid-phase microextraction was combined with high-performance liquid chromatography using a diode array as the detector (HPLC-DAD) for both the separation and determination of three different UV blockers, namely octocrylene, ethylhexyl methoxycinnamate, and avobenzone. The optimum conditions for the extraction were found to be as follows: Stearic acid magnetic nanoparticles (20 mg) as the sorbent, acetonitrile (100 mu L) as the eluent, as well as a sample pH of 2.50, adsorption and desorption time of 1.0 min, with a 3.0 mL sample volume. The limits of detection were as low as 0.05 mu g mL(-1). The coefficient of determination (R-2) was above 0.9950, while the percentages of relative recoveries (%RR) were between 81.2 and 112% for the three UV blockers from the environmental water samples and sunscreen products.
Keywords: dispersive solid-phase microextraction; HPLC-DAD; magnetic nanoparticles; sunscreen products; UV blockers; HYDROPHOBIC ORGANIC-COMPOUNDS; NYLON 6 COMPOSITE; LIQUID-CHROMATOGRAPHY; MASS-SPECTROMETRY; SUNSCREEN AGENTS; EXTRACTION; FILTERS; WATER; PRODUCTS; ACID; Environmental Sciences & Ecology; Public, Environmental & Occupational Health